Pengaruh Harga yang Dipersepsikan, Kualitas Layanan, dan Citra Perusahaan terhadap Loyalitas Pelanggan: Studi Kasus di PT. Evergreen Shipping Agency Indonesia Palembang - Chairunnisah, Firdha Wani; Maulana, Ahmad; Shihab, Muchsin Saggaff (Penerbit Goodwood, 2024)
Purpose: This study is to determine the influence of perceived price, service quality and company image on customer loyalty with customer satisfaction as intervening variable on PT. Evergreen Shipping Agency Indonesia Palembang Methodology: This research uses qualitative data in the form of questionnaire results which are then processed into quantitative data using SmartPLS with 126 people customers of PT. Evergreen Shipping Agency Indonesia Palembang was used as sample Results: The research results show that only service quality and company image influence customer satisfaction and only customer satisfaction and company image have a significant effect on customer loyalty. The corporate image variable has the strongest influence on customer loyalty, while service quality is the variable that has the highest level of significance with the customer satisfaction variable Limitations: The limitation of this study is only focus on perceived price, service quality and company image on customer loyalty with customer satisfaction as intervening variable on PT. Evergreen Shipping Agency Indonesia Palembang Contribution: This research is expected to provide deeper insight into the effect of perceived price, service quality, corporate image to customer loyalty with customer satisfaction as intervening variable